Design, fabrication and modelling of soft robots with novel actuation and materials - Chang, Jung-Che (2025)
Soft robots are gaining attention due to their potential for safe human-robot interactions and delicate operations while maintaining low commercial costs. However, challenges remain in promoting the use of electroactive polymers (EAPs), particularly in improving product quality (particularly in behaviour consistency and product lifetime) and developing dynamic models that enable coordination between multiple actuators.